2021
DOI: 10.1155/2021/1490709
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Analysis of Video-Assisted Thoracoscopic Surgery for Resection of Solitary Pulmonary Nodules and Influencing Factors in the Diagnosis of Benign and Malignant Nodules

Abstract: Purpose. This is a retrospective research comparing the clinical outcomes of single-hole versus multi-hole video-assisted thoracoscopic surgical (VATS) resection for solitary pulmonary nodules (SPN) and examining the factors influencing the diagnosis of benign and malignant pulmonary nodules. Method. We collected the clinical data, surgical status, outcomes, and corresponding imaging features of 317 patients with SPN who were surgically resected by VATS and diagnosed as benign or malignant by pathology in our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In 2011, Gonzalez-Rivas reported the first case of UVATS lobectomy [ 10 ]. UVATS represents a further development of classic VATS under the concept of minimally invasive and rapid recovery, with advantages such as reduced incision size, improved field of view, and reduced chest wall and intercostal nerve injuries compared to multi-port VATS [ 11 ]. However, UVATS also presents challenges due to restrictions on the instruments used, including the thoracoscope [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, Gonzalez-Rivas reported the first case of UVATS lobectomy [ 10 ]. UVATS represents a further development of classic VATS under the concept of minimally invasive and rapid recovery, with advantages such as reduced incision size, improved field of view, and reduced chest wall and intercostal nerve injuries compared to multi-port VATS [ 11 ]. However, UVATS also presents challenges due to restrictions on the instruments used, including the thoracoscope [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“… 6 Subsequent research has shown UVATS to be preferable to multi-portal VATS, 7 , 8 offering benefits like less blood loss and quicker postoperative recovery. 9 , 10 However, UVATS faces scrutiny over technical challenges, particularly the limited space from a single-port entry that can affect instrument handling, leading to issues with bleeding control, suturing, and clear visualization. 11 , 12 These limitations can extend the learning period and increase the complexity of the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%